Impact of Microstructure of Cathode MPL on Interface Water Transport and Power Generation Characteristics of PEFC. (24th November 2015) - Tanaka, Kentaro; Okuhata, Go; Nakamura, Takuya; Nishida, Kosuke
Abstract : It is well known that water flooding in porous electrode of polymer electrolyte fuel cells (PEFCs) leads to severe performance degradation. Microporous layer (MPL) employed between cathode catalyst layer (CL) and gas diffusion layer (GDL) helps to alleviate water accumulation at CL/GDL interface. The aim of this study was to investigate the effect of carbon black (CB) loading of MPL on its microstructure, the interfacial water transport and the power generation characteristics of a PEFC. The pore structure of MPL was analyzed by SEM/EDX and mercury intrusion porosimetry. Furthermore, the water droplet behavior in the cathode electrode was optically visualized using a transparent cell. It was found that MPL addition accelerates water discharge through electrode and improves cell performance. In addition, high CB loading in MPL decreases condensation rate of product water at cathode CL and effectively reduces water flooding at CL/MPL interface.